Study guide to accompany University physics : Arfken, Griffing, Kelly, Priest - Houk, T. William (Academic Press, 1984)
EXAMPLE PROBLEMS; PROBLEMS; Chapter 22. Thermal Properties of Matter; PREVIEW; SUMMARY; EXAMPLE PROBLEMS; PROBLEMS; Chapter 23. Heat Transfer; PREVIEW; SUMMARY; EXAMPLE PROBLEMS; PROBLEMS; Chapter 24. The Second Law of Thermodynamics; PREVIEW; SUMMARY; EXAMPLE PROBLEMS; PROBLEMS; Chapter 25. Kinetic Theory; PREVIEW; SUMMARY; EXAMPLE PROBLEMS; PROBLEMS; Chapter 26. Electric Charge; PREVIEW; SUMMARY; EXAMPLE PROBLEMS; PROBLEMS; Chapter 27. Electric Field and Gauss' Law; PREVIEW; SUMMARY; EXAMPLE PROBLEMS; PROBLEMS; Chapter 28. Electric Potential; PREVIEW; SUMMARY; EXAMPLE PROBLEMS.